A review of saponin-based nanocarriers for drug delivery - Pathy B. Lokole; Galilée G. Byamungu; Paulin K. Mutwale; Nadège K. Ngombe; Michel K. Mpuza; Virima Mudogo; Rui W.M. Krause; Christian I. Nkanga (Next Nanotechnology)
Nanoparticles (NPs) have been extensively used as smart vehicles for the target delivery of therapeutic, immunotherapeutic, and diagnostic agents. The versatility of NPs applications partly arises from the possibility of manufacturing various NPs types depending on the nature of starting materials. In most cases, amphiphilic materials such as phospholipids, solid lipids, fatty acid derivatives, and blends of oils/surfactants, are used to make distinct NPs, namely liposomes, solid lipid nanoparticles (SLNs), nanostructured lipid carriers (NLCs), micelles, and nanoemulsions, respectively. In the pipeline of raw materials, saponins have emerged as a promising alternative for NPs formulation. Saponins are plant-derived secondary metabolites (phytochemicals) with excellent amphiphilic properties, which allow them to play crucial roles in nanotechnology, including their usage as reagents for micellar preparation as well as stabilizing agents for several NPs. Saponin-based NPs have been used to improve the solubility, and pharmacological profile of various active ingredients, encompassing vaccines, owing to inherent immunostimulant/adjuvant properties of saponins. In this review, we mainly discuss the state of the art in biomedical and pharmaceutical applications of saponin-containing NPs, focusing on using saponins as raw materials to make original NPs or as adjuvants for improving already established NPs. The physicochemical properties of saponins have been highlighted, before describing putative nano-formulations with huge promise for drug delivery and vaccine development. The opportunities and challenges pertaining to saponins-containing NPs have been pointed out to set the stage for establishing saponins as an intriguing raw material for the effective translational development of revolutionary nanomedicines.